Green Sukuk sebagai Instrumen Pembiayaan Infrastruktur Berkelanjutan: Analisis Mekanisme dan Dampak Lingkungan Global - Arshy Dhamayanti; Sarpini (Jurnal Ekonomi Islam, 2025)
This study analyzes the mechanism of green sukuk issuance to finance sustainable infrastructure projects in Indonesia and evaluates its global environmental impact, placing it within the principles of Islamic finance. Using a qualitative literature review approach, this study synthesizes data from academic journals, books, official reports, and institutional publications to dissect the structure of sukuk, including ijarah-based contracts through Special Purpose Vehicles (SPVs), and allocations to sectors such as renewable energy, sustainable transportation, and climate resilience. Key findings reveal Indonesia's pioneering role, exemplified by the world's first green sukuk worth USD 1.25 billion in 2018, which raised more than IDR 78.5 trillion in issuances by 2024 and prevented more than 10 million tons of CO2e emissions, primarily through transportation and energy projects. Empirical contributions highlight the effectiveness of green sukuk in mobilizing riba-free funds, attracting millennial investors (56% participation), and advancing Sustainable Development Goals, while underscoring challenges such as the limited availability of skilled human resources for transparent impact reporting. The implications emphasize the need to improve eligibility standards, diversify underlying assets, and certify human resources to maintain Indonesia's leadership in sharia-compliant sustainable finance, while offering a model for the global green transition.